Photosynthetic response to fluctuating environments and photoprotective strategies under abiotic stress - Yamori, Wataru (Journal of plant research, 2016)
Plants in natural environments must cope with diverse, highly dynamic, and unpredictable conditions. They have mechanisms to enhance the capture of light energy when light intensity is low, but they can also slow down photosynthetic electron transport to prevent the production of reactive oxygen species and consequent damage to the photosynthetic machinery under excess light. Plants need a highly responsive regulatory system to balance the photosynthetic light reactions with downstream metabolism. Various mechanisms of regulation of photosynthetic electron transport under stress have been proposed, however the data have been obtained mainly under environmentally stable and controlled conditions. Thus, our understanding of dynamic modulation of photosynthesis under dramatically fluctuating natural environments remains limited. In this review, first I describe the magnitude of environmental fluctuations under natural conditions. Next, I examine the effects of fluctuations in light intensity, CO 2 concentration, leaf temperature, and relative humidity on dynamic photosynthesis. Finally, I summarize photoprotective strategies that allow plants to maintain the photosynthesis under stressful fluctuating environments. The present work clearly showed that fluctuation in various environmental factors resulted in reductions in photosynthetic rate in a stepwise manner at every environmental fluctuation, leading to the conclusion that fluctuating environments would have a large impact on photosynthesis.